1960
DOI: 10.1144/gsjgs.116.1.0269
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Palaeozoic Rocks of South-West Murrisk, Ireland

Abstract: The general geology of an area of Ordovician and Silurian rocks in North Connemara is described. The oldest strata are the Arenigian Sheefry Grits, a thick marine series of slates and greywackes derived from the south. Many of the beds exhibit perfect grading; they are thought to be the deposits of turbidity currents. The Glenummera Slates follow conformably, and are succeeded by the deltaic Mweelrea Grit series, of Middle Ordovician age. Marked facies changes show that the source of sediment lay to the south,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

1961
1961
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 9 publications
3
49
0
Order By: Relevance
“…The Mweelrea Formation occupies the core of the Mweelrea syncline, a gently plunging E-W synclinorium. Six major ignimbrite tuff bands occur within the Mweelrea Formation (Dewey, 1963), which vary in thickness up to 10 m. However, they are not all laterally continuous (Stanton, 1960;Dewey, 1963). Sampling was therefore restricted to four of the more laterally continuous bands.…”
Section: Geological Setting and Samplingmentioning
confidence: 99%
“…The Mweelrea Formation occupies the core of the Mweelrea syncline, a gently plunging E-W synclinorium. Six major ignimbrite tuff bands occur within the Mweelrea Formation (Dewey, 1963), which vary in thickness up to 10 m. However, they are not all laterally continuous (Stanton, 1960;Dewey, 1963). Sampling was therefore restricted to four of the more laterally continuous bands.…”
Section: Geological Setting and Samplingmentioning
confidence: 99%
“…The formation links the underlying and disparate successions of the northern and southern margins of the basin, now exposed in the opposing limbs of the Mweelrea Syncline (Figure 1; Graham et al, 1985). The sandstones and conglomerates are punctuated by five or six ignimbrites, which allow for detailed correlation along strike and across the syncline (Stanton, 1960;Riggs and McConnell, unpublished data).…”
Section: Geological Settingmentioning
confidence: 99%
“…This cordillera persisted throughout Ordovician and Silurian times and it is considered likely that the Connemara antiform, and probably also the WNW antiform south of Clifden, were initially developed at this time. Stanton (1960) has demonstrated that the NW-SE Maam Faults (Fig. 1) were moving during the deposition of the Partry Series with a moderate downthrow to the northeast.…”
Section: The Structural Sequencementioning
confidence: 98%